Affective Factors: Motivation in Second Language Acquisition, Case of Uzbek Learner (Eurasian Journal of Learning and Academic Teaching, 2022)
The article gives an overview of various learning affective factors in second language acquisition, particularly focusing on motivation and represents some data about one of the Uzbek learner’s cases with research method and findings.